2019
DOI: 10.1080/21501203.2019.1705929
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of Tephrosia vogelii against selected pathogenic fungi and bacteria strains

Abstract: Candida albicans and Cryptococcus neoformans are dangerous pathogens causing fungal diseases. C. albicans and C. neoformans developed resistance to fungicides such as fluconazole. Similarly, pathogenic bacteria Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and Salmonella typhi have become resistant to antibiotcs such as methicillin. Thus, searching for alternative antimicrobial agents is inevitable. Tephrosia vogelii used traditionally for management of fungal and bacterial diseases is potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Also, this study on phytochemical screening revealed the absence of alkaloids and anthraquinones suggesting that these medicinal properties of Tephrosia vogelii found particularly in Tanzania may be branded mainly by tannins, steroids, terpenes, flavonoids and glycosides. On the other hand, the chemical nature of the phytochemicals analysed from this medicinal plant clearly coincides with the antimicrobial activities and ectoparasitic activities reported in the previous studies (Alamgir, 2017;Arif et al, 2011;Badri et al, 2017;Kenechukwu et al, 2012;Irawan et al, 2018;Makoshi & Arowolo, 2011;Mbunde et al, 2016;Mlozi et al, 2020;Murtaza et al, 2015;Nneka & Jude, 2012;Okpogba et al, 2019;Omodamiro & Amechi, 2013;Pietta, 2000;Priya et al, 2014;Ramawat & Mérillon, 2013;Sahu et al, 2014;Samuel et al, 2019;Sasidharan et al, 2011;Singh et al, 2017;Swamy et al, 2015;Trakranrungsie, 2011).…”
Section: Phytochemical Investigationsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, this study on phytochemical screening revealed the absence of alkaloids and anthraquinones suggesting that these medicinal properties of Tephrosia vogelii found particularly in Tanzania may be branded mainly by tannins, steroids, terpenes, flavonoids and glycosides. On the other hand, the chemical nature of the phytochemicals analysed from this medicinal plant clearly coincides with the antimicrobial activities and ectoparasitic activities reported in the previous studies (Alamgir, 2017;Arif et al, 2011;Badri et al, 2017;Kenechukwu et al, 2012;Irawan et al, 2018;Makoshi & Arowolo, 2011;Mbunde et al, 2016;Mlozi et al, 2020;Murtaza et al, 2015;Nneka & Jude, 2012;Okpogba et al, 2019;Omodamiro & Amechi, 2013;Pietta, 2000;Priya et al, 2014;Ramawat & Mérillon, 2013;Sahu et al, 2014;Samuel et al, 2019;Sasidharan et al, 2011;Singh et al, 2017;Swamy et al, 2015;Trakranrungsie, 2011).…”
Section: Phytochemical Investigationsupporting
confidence: 86%
“…These pieces of evidence generated from our GC-MS analysis and literature suggest that among other, the presence of identified flavonoids, sesquiterpenes and fatty acids contributes largely to the antimicrobial activities (Mlozi et al, 2020). Moreover, these phytocompounds sustenance reported ethnopharmacological possessions of Tephrosia vogelii.…”
Section: Phytochemical Investigationmentioning
confidence: 63%
See 1 more Smart Citation
“…In serial dilution experiments (1024–32 μg/mL), RHA did not show antimicrobial activity against investigated bacteria, yeast, or filamentous fungi. Despite studies confirming the antimicrobial activity of alcoholic extracts from other Tephrosia species, it has an MIC > 2.5 mg/mL [ 116 , 117 ], reaching MIC = 200 mg/mL [ 118 ]. These results suggest that the antimicrobial formulations of Tephrosia must be administered in high concentrations for the manifestation of their activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been used traditionally in fishing activities and as traditional pesticides in local agricultural activities for many decades [17][18][19]. The pharmacological study of methanolic extracts of T. vogelii revealed its antimicrobial activities [16,20]. The pharmacological studies on bioactive compounds such as rotenoids and steroids from T. vogelii revealed the potentiality of such compounds for development of pesticides and insecticide [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%